Individual winning consistency metrics predict match outcome and podium performance in freestyle senior world wrestling - López-González, D. E. (International Journal of Wrestling Science, 2023)
Purpose. This study introduces the concept of Individual Winning Consistency (IWC) as an Opponent Quality metric in Freestyle Wrestling. The research aims to address two primary questions: a) Can a higher IWC for a contender, calculated prior to a match-up, reliably predict the match result? b) Can the IWC effectively predict Medal Performance?